Nanoparticles for Detection and Treatment of Peripheral Arterial Disease. Issue 32 (27th June 2018) - Noukeu, Linda C.; Wolf, Joseph; Yuan, Baohong; Banerjee, Subhash; Nguyen, Kytai T.
Abstract: Peripheral arterial disease (PAD) is defined as a slow, progressive disorder of the lower extremity arterial vessels characterized by chronic narrowing that often results in occlusion and is associated with loss of functional capacity. Although the PAD occurrence rate is increasing in the elderly population, outcomes with current treatment strategies are suboptimal. Hence, there is an urgent need to develop new technologies that overcome limitations of traditional modalities for PAD detection and therapy. In this Review, the application of nanotechnology as a tool that bridges the gap in PAD diagnosis and therapy is in focus. Several materials including synthetic, natural, biodegradable, and biocompatible materials are used to develop nanoparticles for PAD diagnostic and/or therapeutic applications. Moreover, various recent research approaches are being explored to diagnose PAD through multimodality imaging with different nanoplatforms. Further efforts include targeted delivery of various therapeutic agents using nanostructures as carriers to treat PAD. Last, but not least, despite being a fairly new field, researchers are exploring the use of nanotheranostics for PAD detection and therapy. Abstract : This Review focuses on the applications of nanoparticles used in the detection and treatment of peripheral arterial disease (PAD). Three main approaches: 1) application of nanoparticles for PAD detection, 2) application of nanoparticles for treatment of PAD, and 3) application of nanoparticles as nanotheranostics for the detection and therapy for PAD, are further discussed in detail.